Suco de laranja potencialmente prebiótico, síntese em escala ampliada e efeitos na microbiota e na expressão de genes relacionados a inflamação - Leite, Ana Karoline Ferreira (2024)
The development of new prebiotic foods and their relationship with human health are topics that have been strongly explored. An option for producing prebiotic juices is the synthesis of these compounds directly in the juice. However, there is limited knowledge about scaling up this process and its potential beneficial effects at the intestinal level. Thus, using the enzyme dextransucrase, this work aimed to evaluate the effect of temperature and agitation on the synthesis of oligosaccharides and dextran in orange juice in increased volume, as well as the effect of the juice on the human intestinal microbiota composition, on epithelial barrier of Caco-2/TC7 intestinal cells and on expression of target genes. Aiming to achieve a better performance on the mixing system, especially the homogeneity of the medium and the carbohydrate diffusivity, the synthesis was conducted directly on the orange juice in magnetic and mechanical stirred reactors at 25 and 30 ºC (MAG25, MEC25, MAG30 and MEC30) for 24 h. The juices produced were submitted to in vitro digestion, followed by fermentation by the colonic microbiota of two donors, one vegetarian (A) and the other omnivorous (B), under anaerobic conditions (37 °C/48 h). Finally, the effect of orange juice without (SL) and with oligosaccharides and dextran (SLP) was evaluated, before and after in vitro digestion (SLD and SLPD) on viability, transepithelial electrical resistance (TEER) and expression of genes related to inflammation (IL-8, TNF-α, NF-κB-1 and COX-2), tight junctions (ZO-1) and sugar metabolism (GLUT-2, SLGT-1 and GLUT-5) in Caco-2/TC7 intestinal cells. The concentration of reducing sugars (AR) into the juice reduced at 25 °C, due to the use of RS in the production of oligosaccharides and dextran, and increased in syntheses conducted at 30 °C, an indication of hydrolysis. Furthermore, a higher concentration of oligosaccharides and dextran was identified in juices synthesized at 25 °C. In terms of agitation, magnetic agitation increased dextran synthesis, while the type of agitation did not interfere on the production of oligosaccharides at 25 ºC/6 h. Despite the excellent results for MAG25, MEC25 was selected for next steps because mechanical stirred reactors are more suitable for large-scale production. The donors presented different profiles of oligosaccharide consumption and acid production, with rapid and complete consumption of oligosaccharides by donor B, in addition to high propionate accumulation. Oligosaccharides and dextran present in the digested juice were consumed by the human fecal microbiota of both donors, with consequent production of high concentrations of lactate and acetate, followed by butyrate, propionate and isobutyrate. The microbiota of donor A showed a high relative abundance of Lactobacillus ruminis (44.96%), while Bifidobacterium adolescentis was the main bacteria in the microbiome of donor B (41.73%) after 24 h. The abundance of beneficial microorganisms such as Bacteroides xylanisolvens was also favored by functional orange juice (6.08 and 8.52%), but a reduction in some species of Clostridia sp was observed. In Caco-2/TC7 cells, SLP increased cell viability and TEER values compared to SL. After digestion, SLPD reduced damage and structural losses in the cell layer compared to SLD. SLPD, at 1.25 % concentration, reduced the expression of inflammation-related genes and did not affect the expression of the ZO-1 gene. However, 2.5% SLPD increased the ZO-1 mRNA levels. No changes were observed on the expression of sugar transport-related genes. In this sense, orange juice containing oligosaccharides and dextran improved the composition and metabolic activity of the human colonic microbiota and may contribute to reducing intestinal inflammation and improving barrier function, being an alternative to the functional food market.